Assessing attentional biases with stuttering. Issue 1 (14th July 2015) - Lowe, Robyn; Menzies, Ross; Packman, Ann; O'Brian, Sue; Jones, Mark; Onslow, Mark
Abstract: Background: Many adults who stutter presenting for speech treatment experience social anxiety disorder. The presence of mental health disorders in adults who stutter has been implicated in a failure to maintain speech treatment benefits. Contemporary theories of social anxiety disorder propose that the condition is maintained by negative cognitions and information processing biases. Consistent with cognitive theories, the probe detection task has shown that social anxiety is associated with an attentional bias to avoid social information. This information processing bias is suggested to be involved in maintaining anxiety. Evidence is emerging for information processing biases being involved with stuttering. Aims: This study investigated information processing in adults who stutter using the probe detection task. Information processing biases have been implicated in anxiety maintenance in social anxiety disorder and therefore may have implications for the assessment and treatment of stuttering. It was hypothesized that stuttering participants compared with control participants would display an attentional bias to avoid attending to social information. Methods & Procedures: Twenty‐three adults who stutter and 23 controls completed a probe detection task in which they were presented with pairs of photographs: a face displaying an emotional expression—positive, negative or neutral—and an everyday household object. All participants were subjected to a mild social threat induction being told they would speak to a small group of people on completion of the task. Outcomes & Results: The stuttering group scored significantly higher than controls for trait anxiety, but did not differ from controls on measures of social anxiety. Non‐socially anxious adults who stutter did not display an attentional bias to avoid looking at photographs of faces relative to everyday objects. Higher scores on trait anxiety were positively correlated with attention towards photographs of negative faces. Conclusion & Implications: Attentional biases as assessed by the probe detection task may not be a characteristic of non‐socially anxious adults who stutter. A vigilance to attend to threat information with high trait anxiety is consistent with findings of studies using the emotional Stroop task in stuttering and social anxiety disorder. Future research should investigate attentional processing in people who stutter who are socially anxious. It will also be useful for future studies to employ research paradigms that involve speaking. Continued research is warranted to explore information processing and potential biases that could be involved in the maintenance of anxiety and failure to maintain the benefits of speech treatment outcomes.